Impact from the Activity Physical It is Leisure in practitioners in Esports - Lourenço, Carla Cristina Vieira; Erick Burhaein, Erick Burhaein (JUMORA: Jurnal Moderasi Olahraga, 2024)
The purpose of this work is to identify the contribution of Esports in promoting Physical Activity and Leisure. This is an exploratory and descriptive research conducted through The bibliographic analysis using The set of databases. The study was based on 551 articles, of which 14 were selected for the development of this work, with 6 of them being analyzed in detail. As a conclusion, it was observed that Esports play a significant role in promoting physical activity and leisure, providing numerous benefits for the health, well-being, and performance of its practitioners. From this research, we can find out the influence of esports on the promotion of physical activity, namely leisure, such as the following some positive impacts and negative impacts on the lives of practitioners. In the context of promoting physical activity and leisure, there are four areas where Esports can play a relevant role: new technologies, active electronic games, media, and the potential for physical activity to improve performance. Considering the indicators, it is essential to adopt strategies aligned with the activity physical, optimizing to the benefits in each one from them.